Resilience Training Programs in Organizational Contexts: A Scoping Review - Scheuch, Ianina; Peters, Natalie; Lohner, Max S.; Muss, Caroline; Aprea, Carmela; Fürstenau, Bärbel (Frontiers in Psychology, 2021)
The importance of resilience for employees’ well-being and performance at work has grown steadily in recent years. This development has become even more pronounced through the recent COVID-19 pandemic and its consequences, including major changes in occupational settings. Although there is increasing interest in resilience in general and a growing number of publications focusing on the development of resilience in particular, many questions remain about resilience training, especially in organizational contexts. The purpose of this scoping review is to uncover what is known about resilience training in organizational contexts. A systematic search of four databases for articles published through 2021 was conducted. A total of 48 studies focusing on resilience training programs in organizational contexts were included in this review. The review provides relevant insights into resilience training programs by focusing on program characteristics, target group, study design, and outcomes. Based on the results, the main aspects that concern the development of resilience training programs for organizational settings and requirements for the study design for empirical investigation were summarized. The results of the review highlight possible directions for future research and offer useful insights for resilience-enhancing training programs in organizations.